PENGARUH PENGARAHAN TERHADAP KINERJA PEGAWAI PADA KANTOR SEKERTARIAT DAERAH OGAN KOMERING ULU - Fauzan, Ahmad; Kurniawan, Setia; Yusdi, Yudikal (YHMM PUBLISHING, 2024)
The availability of quality human resources and high work ethics is the main capital of an organization to be able to be on par with other organizations. Without the personal efforts of each individual to strive to progress without being forced, the organization means nothing. At the Regional Secretariat Office of Ogan Komering Ulu Selatan, it turns out that the Direction has not been implemented properly so that employee performance is not optimal. The problem faced is how the Direction influences employee performance at the Regional Secretariat Office of Ogan Komering Ulu Selatan. The purpose of this study is to determine the influence of Direction on employee performance at the Regional Secretariat Office of Ogan Komering Ulu Selatan and is useful as a reference for further research on Direction and Employee Performance. The hypothesis proposed is that Direction has a positive effect on employee performance at the Regional Secretariat Office of Ogan Komering Ulu Selatan. Data collection and processing using literature studies and field studies using observation, questionnaires, interviews and documentation. From the results of the discussion, the correlation between Direction in efforts to improve employee performance at the Ogan Komering Ulu Selatan Regional Secretariat Office obtained an r figure of 0.57. After consulting with conservative standards, it is between 0.400-0.599 which is included in the moderate correlation. So it can be said that there is a moderate influence between Direction on employee performance at the Ogan Komering Ulu Selatan Regional Secretariat Office.